The effect of slope level and hydroseeding formula on the growth of Cyperus brevifolius and Pueraria javanica seedlings - Zairina Anisa; Yani Quarta Mondiana (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Zairina A, Mondiana YQ. 2020. The effect of slope level and hydroseeding formula on the growth of Cyperus brevifolius and Pueraria javanica seedlings. Biodiversitas 21: 5008-5012. The aim of this study was to analyze the effect of the slope level on the growth of green kyllinga (Cyperus brevifolius) and puero (Pueraria javanica) seedling in a hydroseeding formula. The hydroseeding mixture consists of plant seeds, compost, soil conditioner, manure, and water. In addition, to all hydroseeding compositions, guar gum and a local microorganism mix were mixed until colloidal mulch was obtained. This study applied factorial design with slope level dan hydroseeding treatment as independent variables, while seed height, number of shoots, and number of leaves were the dependent variables. Data were replicated four times. The hydroseeding formula had a significant effect on all variables, except for the height of C. brevifolius seedlings. There was a significant interaction effect between the slope level and hydroseeding treatment on the germination rate of both species but the effect of this interaction was not significant on plant height and leaf number. The best germination rates were found in boxes with a slope of 100%. This situation was consistent for both species. This indicated that both species had the potential to be used as pioneer plants in post-landslide reclamation with a slope of 100%.